A literature review of HRQoL and prevalence of fibrodysplasia ossificans progressiva - Sukannya Mahapatra, Pradeep Manohar Muragundi, Srushti Choughule, Arzoo Piruka (Journal of Applied Pharmaceutical Science, 2023)
Fibrodysplasia Ossificans Progressiva (FOP) is an ultrarare genetic disorder and a literature review was undertaken to determine the epidemiology of FOP and its impact on the quality of life of patients. Medline® and Embase® databases were searched for Epidemiology and health-related quality of life information using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. English language studies including FOP patients were included. A total of seven studies were identified reporting the epidemiology and eight studies reporting the humanistic burden associated with FOP. The prevalence of FOP ranged from 0.04 to 1.36 per million population. A higher prevalence of FOP was found in the USA (0.88 per million) and Europe (0.47–1.36 per million) compared to the Asian (0.11 per million) population. Patient-Reported Outcomes Measurement Information System (PROMIS) and 36-Item Short Form Health Survey were the most commonly used instruments in FOP to assess the humanistic burden. Assessed on the PROMIS scale moderate to severe pain (≥4, 0–10 pain scale) was commonly associated with flare-ups of FOP (56%–67% of patients experiencing it), and 45%–74% of these patients also experienced anxiety, depression, or irritability. Variability in the prevalence of FOP was reported across geographies. A significant deterioration in the quality of life secondary to progressive deterioration in physical abilities was observed in FOP, therefore, highlighting the need for effective therapies in this highly unmet disease area.